2016
DOI: 10.1039/c5nr07571h
|View full text |Cite
|
Sign up to set email alerts
|

High second-order nonlinear response of platinum nanoflowers: the role of surface corrugation

Abstract: Platinum nanoflowers (PtNFs) were elaborated using the seed-mediated growth technique applied to monodisperse platinum nanoparticles (∼3.0 nm) synthesized by the chemical reduction method. The X-ray diffraction pattern confirmed the formation of face-centered-cubic platinum nanocrystals. We report the Harmonic Light Scattering (HLS) properties of PtNFs for six different diameters (∼7.0; 8.0; 10.0; 14.0; 20.0 and 31.0 nm). From these HLS data we infer, for the first time, large hyperpolarizability β values of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…Indeed, El Harfouch et al 15 reported first hyperpolarizability values for gold nanospheres and nanorods in the range of 10 −25 −10 −24 esu, about 2 orders of magnitude higher than those for the present gold nanoprisms, in line with data obtained for other plasmonic nanoparticles. 16,32 In order to further support the surface origin of the nonlinearity, the first hyperpolarizabilities were normalized per unit surface area, see Table 2. The value of about (5 ± 2) × 10 −31 esu/nm 2 is obtained.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Indeed, El Harfouch et al 15 reported first hyperpolarizability values for gold nanospheres and nanorods in the range of 10 −25 −10 −24 esu, about 2 orders of magnitude higher than those for the present gold nanoprisms, in line with data obtained for other plasmonic nanoparticles. 16,32 In order to further support the surface origin of the nonlinearity, the first hyperpolarizabilities were normalized per unit surface area, see Table 2. The value of about (5 ± 2) × 10 −31 esu/nm 2 is obtained.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In view of the many merits induced by optofluidics, the microreactors may be also introduced to other APS systems such as nitrogen fixation (e.g., NH 4 ) [ 100 ], CH 4 [ 101 106 ], CO [ 107 111 ], formaldehyde [ 112 113 ], methanol [ 114 116 ], and formic acid [ 117 ]. More profound and meaningful work is expected to appear in the field of optofluidics-based APS since the optofluidic devices are versatile and can be integrated together with other functions, for instance, deoxygenation, temperature control, electricity/magnetic field and pressure [ 118 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Au, Ag and Cu) are working under visible light irradiation, there are also examples of UV-plasmonic metal nanoparticles. For example, platinum (Pt) and many of its alloy nanoparticles exhibit significant plasmonic response in the UV range (< 300nm) [19,20].…”
Section: Configuration Of Cocatalyst Particlesmentioning
confidence: 99%